THE ANALYSIS OF RISK FACTORS OF PURULENT-SEPTIC COMPLICATIONS DEVELOPMENT AFTER ABDOMINAL DELIVERY - A. N. Rymashevsky; J. L. Naboka; M. V. Potapova; E. D. Slyusareva; R. S. Gevorkyan; A. V. Kadetov; L. A. Terekhina (Медицинский вестник Юга России, 2013)
Purpose: estimation of risk factors and degree of their significance in infectious-inflammatory processes development after Cesarean section.Materials and methods: the retrospective medical documentation analysis of 2235 cases of operative delivery.Results: it is established that antibiotic prophylaxis at a Cesarean section during the investigated period was carried out without contemporary risk factors, an individual estimation of qualitative-quantitative structure genital tract microflora and its account antibiotic -sensitivity in 16.2 % of cases led to nonspecific inflammatory complications development in the postnatal period. Contemporary risk factors of inflammatory complications development in abdominal delivery are revealed.Summary: it is necessary to accomplish a working out and introduction of contemporary and scientifically proved algorithm of purulent-septic complications prevention after abdominal delivery in work of obstetric permanent establishment, taking into account modern risk factors.